Aging-Associated Changes to Intrinsic Neuronal Excitability in the Bed Nucleus of the Stria Terminalis Is Cell Type-Dependent - Smithers, Hannah E.; Terry, John R.; Brown, Jon T.; Randall, Andrew D. (Frontiers in Aging Neuroscience, 2017)
Intrinsic neuronal excitability has been reported to change during normal aging. The bed nucleus of the stria terminalis (BNST), a limbic forebrain structure, is involved in fear, stress and anxiety; behavioural features that exhibit age-dependent properties. To examine the effect of aging on intrinsic neuronal properties in BNST we compared patch clamp recordings from cohorts of female mice at two ages, 3-4 months (Young) and 29-30 months (Aged) focusing on 2 types of BNST neurons. Aged Type I neurons exhibited a hyperpolarised resting membrane potential (RMP) of circa-80 mV compared to circa-70 mV in the Young. Type II neurons display hyper-excitability with age reflected in an increase in firing frequency in response to depolarising current injections. A potential source underlying this observation in Type II neurons was a more negative AP threshold in the aged mice. Such age-related changes in intrinsic neurophysiological function are likely to modulate how the limbic system, acting via BNST, shapes function in the HPA-axis.